Las tecnologías de la información y la comunicación y su incidencia en el desarrollo del proceso de enseñanza aprendizaje en el primer año de bachillerato del colegio nacional nocturno Dr. Modesto Chávez Franco de la ciudad de Santa Rosa, periodo 2014-2015 - Pulgarin Sánchez, Juana Nohemy (2015)
The advent of the XXI century frame the way of living and thinking of our society , due to the rapid advancement of information and communications technology , which have been present in all areas of human knowledge , the education field is not the exception as THROUGH the proper use of computer resources in education allows teachers to develop students abilities, skills and criteria enabling them to deal in the workplace and in their daily lives .